Strategies for Targeting Gene Therapy in Cancer Cells With Tumor-Specific Promoters - Montaño-Samaniego, Mariela; Bravo-Estupiñan, Diana M.; Méndez-Guerrero, Oscar; Alarcón-Hernández, Ernesto; Ibáñez-Hernández, Miguel (Frontiers in Oncology, 2020)
Cancer is the second cause of death worldwide, surpassed only by cardiovascular diseases, due to the lack of early diagnosis, and high relapse rate after conventional therapies. Chemotherapy inhibits the rapid growth of cancer cells, but it also affects normal cells with fast proliferation rate. Therefore, it is imperative to develop other safe and more effective treatment strategies, such as gene therapy, in order to significantly improve the survival rate and life expectancy of patients with cancer. The aim of gene therapy is to transfect a therapeutic gene into the host cells to express itself and cause a beneficial biological effect. However, the efficacy of the proposed strategies has been insufficient for delivering the full potential of gene therapy in the clinic. The type of delivery vehicle (viral or non viral) chosen depends on the desired specificity of the gene therapy. The first gene therapy trials were performed with therapeutic genes driven by viral promoters such as the CMV promoter, which induces non-specific toxicity in normal cells and tissues, in addition to cancer cells. The use of tumor-specific promoters over-expressed in the tumor, induces specific expression of therapeutic genes in a given tumor, increasing their localized activity. Several cancer- and/or tumor-specific promoters systems have been developed to target cancer cells. This review aims to provide up-to-date information concerning targeting gene therapy with cancer- and/or tumor-specific promoters including cancer suppressor genes, suicide genes, anti-tumor angiogenesis, gene silencing, and gene-editing technology, as well as the type of delivery vehicle employed. Gene therapy can be used to complement traditional therapies to provide more effective treatments.